Mechanism for Resolving The Crime Of Bullying Performed By Students at Schools In Indonesia - Bustani; Muhammad Hatta; Joelman Subaidi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Bullying in education is a despicable and illegal act. Bullying can hurt the victim both physically and mentally. Perpetrators and victims of bullying in schools are generally still minors, so that the settlement of these cases must pay attention to the rights of children which have been regulated in Law Number 35 of 2014 Jo. Law Number 17 of 2016 concerning Child Protection. In-Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, the mechanism for resolving cases involving children uses a restorative justice approach through a diversionary case settlement mechanism. The diversion mechanism is carried out outside the court (non-litigation) by carrying out mediation between the perpetrator and the victim and attended by both families of the perpetrators and victims, law enforcers, and the community. Diversion must be pursued by law enforcement at every stage of the judiciary, both at the stage of the investigation, prosecution and examination of cases in court. However, if the diversion mechanism fails or the perpetrator of bullying does not meet the requirements for the diversion mechanism, the crime of bullying will be resolved through litigation through juvenile justice.